Respuesta :

leena

Hi there! :)

[tex]\large\boxed{-4}[/tex]

Use PEMDAS (Parenthesis, Exponents, Multiply, Divide, Addition, Subtraction) to simplify:

[tex]\frac{6 - 3(2^{2}-11)+5 }{4-36/3}[/tex]

We can begin by simplifying the numerator and denominator separately:

6 - 3(2² - 11) + 5 =

Exponents:

6 - 3(4 - 11) + 5 =

Multiplication:

6 - 12 + 33 + 5 =

Add and subtract:

32

-------------------

Denominator:

Division:

4 - 36÷3 =

Subtraction:

4 - 12 = -8

Resulting fraction:

[tex]\large{\frac{32}{-8}} = -4[/tex]